2018
DOI: 10.5811/westjem.2017.10.36219
|View full text |Cite
|
Sign up to set email alerts
|

Ruling out Pulmonary Embolism in Patients with High Pretest Probability

Abstract: IntroductionThe American College of Emergency Physicians guidelines recommend more aggressive workup beyond imaging alone in patients with a high pretest probability (PTP) of pulmonary embolism (PE). However, the ability of multiple tests to safely rule out PE in high PTP patients is not known. We sought to measure the ability of negative computed tomography pulmonary angiography (CTPA) along with negative D-dimer to rule out PE in these high-risk patients.MethodsWe analyzed data from a previous prospective ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The presence of false-negative CTPA studies in patients with established pulmonary embolic disease observed by Moores et al [ 8 ] has been reaffirmed by several retrospective studies and systematic reviews [ 10 12 ]. In a cohort of 201 patients deemed to be at high risk for CTEPD (Wells score ≥6), Akhter et al [ 10 ] identified 16 patients with evident PE despite a negative CTPA study.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The presence of false-negative CTPA studies in patients with established pulmonary embolic disease observed by Moores et al [ 8 ] has been reaffirmed by several retrospective studies and systematic reviews [ 10 12 ]. In a cohort of 201 patients deemed to be at high risk for CTEPD (Wells score ≥6), Akhter et al [ 10 ] identified 16 patients with evident PE despite a negative CTPA study.…”
Section: Introductionmentioning
confidence: 86%
“…The presence of false-negative CTPA studies in patients with established pulmonary embolic disease observed by Moores et al [ 8 ] has been reaffirmed by several retrospective studies and systematic reviews [ 10 12 ]. In a cohort of 201 patients deemed to be at high risk for CTEPD (Wells score ≥6), Akhter et al [ 10 ] identified 16 patients with evident PE despite a negative CTPA study. Systematic reviews conducted by Hogg et al [ 11 ] and Kligerman et al [ 12 ] have demonstrated that false-negative CTPA studies is a ubiquitous issue in the investigation and diagnosis of CTEPD.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Pulmonary embolism (PE) is a common life-threatening condition which contributes to the global burden of cardiovascular diseases in terms of morbidity and mortality (1)(2)(3)(4)(5). The 30-day mortality rate due to PE exceeds 15% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the operator-dependent and technical challenges of imaging the right heart have limited this modality [ 7 ]. As the frontier imaging modality for APE diagnosis [ [8] , [9] , [10] , [11] ], computed tomography pulmonary angiography (CTPA) has increasingly been established. CTPA provides the advantage of a more comprehensive assessment of the severity of obstruction of the pulmonary artery compared with echocardiography, which can simultaneously diagnose RVD, related underlying pulmonary disease, and other causes of acute chest pain [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%